Nation State in Multiethnic Society - Tapiheru, J.E.S. (2011)
Focusing on ethnic diversity, this dissertation investigates on how diversity is governed within a polity known as nation state. This dissertation sees nation state as basically a hegemonic formation through which the ethnicity of certain groups are constructed and governed. This study investigates how this nation state as hegemonicformation as discursive process that continuously renewed, negotiated, and redefinedwithin the dynamic realities it creates in the cases of Indonesia and Sri Lanka under their current respective administration. These two countries are chosen as the cases for this study since they have been struggling to govern the diverse groups within their societies. Some of these groups demand political recognition as distinct entities to the rest of the nations and sometimes lead to demand for recognition for their right for self-determination. This dissertation analyses how the certain notions of Indonesia and Sri Lanka as nation states are constructed to hegemonize those groups constructed as ethnic groups.